Fluid Lubricated Dexterous Finger Mechanism for Human-Like Impact Absorbing Capability - Kim, Yong-Jae; Yoon, Junsuk; Sim, Young-Woo (IEEE robotics and automation letters)
This letter presents a novel three degree-of-freedom finger mechanism that features excellent impact absorbing performance, high force, and precision comparable to human hands. Inspired by human fingers, it has a simple structure with a minimum number of rigid components: seven rigid frames, several polymer wires, and flexible sheets. For impact absorption, rolling contact joints with a center ligament, instead of conventional revolute joints with bearings or bushings, were used. While this mechanism can be dislocated in the event of off-axis bending or twisting force and impact, it can return afterward without degrading precision. To achieve precise manipulation performance, a unique tendon guiding structure, which enables accurate kinematic modeling even though it is composed of soft and flexible materials, is proposed. To prevent loss of precision and robustness against friction, the whole mechanism is covered by an artificial skin and filled with lubrication liquid, which is similar to human synovial fluid. The developed finger mechanism can exert 40 N fingertip force in a straight pose and has 0.2 mm repeatability of fingertip position under multiple impacts. Various experiments including button clicking and wheel rotation of a computer mouse demonstrated the performance and potential usefulness of the proposed mechanism.